The Provincial Letters Pense'es Scientific Treatises - Pascal, Blaise; Edited by Hutchin, Robert Maynard (Chicago Encyclopedia Britannica Inc, 1952)
Pensées (Thoughts) is a collection of Pascal's notes and ideas for a book in defense of faith in a rational world. These fragments give evidence of a profoundly original thinker who has resolved his conflict between a scientific mind demanding proof and a spiritual position maintained by faith.
Keywords: Catholic Church -- French literature -- Theology, Doctrinal